2021
DOI: 10.1002/1878-0261.12964
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo genome‐wide shRNA screen identifies BCL6 as a targetable biomarker of paclitaxel resistance in breast cancer

Abstract: Paclitaxel is a common breast cancer drug; however, some tumors are resistant. The identification of biomarkers for paclitaxel resistance or sensitivity would enable the development of strategies to improve treatment efficacy. A genome-wide in vivo shRNA screen was performed on paclitaxel-treated mice with MDA-MB-231 tumors to identify genes associated with paclitaxel sensitivity or resistance. Gene expression of the top screen hits was associated with tumor response (resistance or sensitivity) among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Naturally occurring cyclic diterpenoids, such as tanshinones, paclitaxel, or platensimycin, possess antimicrobial and antitumor activities. Among them, paclitaxel has been extensively used as an anticancer drug ( Vranová et al, 2013 ; Sultan et al, 2021 ). Ginkgo lactone can be used to treat cardiovascular disease as a natural platelet activation antagonist ( Liu et al, 2018 ) and is also employed to treat Alzheimer’s disease ( Sarkar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring cyclic diterpenoids, such as tanshinones, paclitaxel, or platensimycin, possess antimicrobial and antitumor activities. Among them, paclitaxel has been extensively used as an anticancer drug ( Vranová et al, 2013 ; Sultan et al, 2021 ). Ginkgo lactone can be used to treat cardiovascular disease as a natural platelet activation antagonist ( Liu et al, 2018 ) and is also employed to treat Alzheimer’s disease ( Sarkar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…308 BCL6 expression has also been linked to paclitaxel resistance in breast cancer. 309 ChIP-seq for BCL6 in breast cancer cell lines revealed a different pattern of binding to that seen in GC B cells and lymphoma. 307 Around 50% of the genes bound by BCL6 in breast cancer were also bound by BCL6 in lymphoma, indicating at least some overlap in BCL6 function.…”
Section: 27: Bcl6 In Other Cancersmentioning
confidence: 90%
“…Previous studies have shown that BCL6 is involved in resistance to several types of anti-cancer therapies in multiple cancers. 207,210,295,302,309,311,350,351,406 In GBM cell lines, inhibition of BCL6 significantly increases the efficacy of TMZ and IR. 207,210 However, little was known about how BCL6 is involved in these therapy responses.…”
Section: Bcl6 Involvement In Treatment Responsesmentioning
confidence: 99%
See 1 more Smart Citation